Penentuan Kebutuhan Pupuk Kalium dengan Uji K-Tanah untuk Tanaman jagung di Typic Kandiudox - Sutriadi, Mas Teddy; Setyorini, Diah; Nursyamsi, Deddi; Murni, Andarias Makka (JOURNAL OF TROPICAL SOILS, 2008)
Fertilization of K is very important to increase product agriculture besides fertilization of N and P. In this time usage fertilizer not yet proportional and rational, such as those which happened in usage rice field fertilizer of K for the crop of paddy tend to excessively. The other way in the upland needing more fertlizer but fertilized slimmer or is not fertlized K. Proportional and rational fertilization can reach if pay attention the nutrients dynamics and soil status, and also requirement of nutrient for this crop to reach optimum production. This approach can be executed better and profit if fertilization recommendation based on by result of research soil testing.  Research goal to to determine requirement of K fertilizer  for maize in Typic Kandiudox. The experiments used split-plot design, as main plot are five status nutrients and as sub plot are five treatments of K levels, three replications. The levels of K treatment were 0, 20, 40, 80, and 160 kg K/ha from KCl fertilizer and as indicator crop was maize cultivar P-12.  The result showed that NH4OAc. pH 4,8, NH4OAc. pH 7,0, and HCl 25% were selected extraction methode to estimate K fertilizer requirement  for Maize (Zea mays L.) in Typic Kandiudox and NH4OAc. 1 N pH 4,8 was the best extractan, because get highest coefisien corelation. The K status can be grouped into three classes of availability of K are low, medium, and high with the critical limit for each extractan are 5,0; 10,0; dan 130 mg kg-1 K2O for NH4OAc. 1 N pH 4,8, NH4OAc. 1 N pH 7,0, and HCl 25 % extractants respectively. Optimum dosages of K fertilizer was 150 kg ha-1 and 75 kg ha-1 KCl each for the low and medium status and do not be fertilized for the high status.